Days with frog and toad - Lobel, Arnold (New York : Harper & Row, 1979)
Frog and Toad spend their days together, but find sometimes it's nice to be alone.
G2
Keywords: Frogs -- Fiction; Toads -- Fiction; Friendship -- Fiction